Two-dimensional nanosheets functionalized water-borne polyurethane nanocomposites with improved mechanical and anti-corrosion properties. Issue 12 (1st December 2020) - Gao, Xiaoyan; Bilal, Muhammad; Ali, Nisar; Yun, Shan; Wang, Jinquan; Ni, Lingli; Cai, Peng
Abstract: Waterborne polyurethanes (WPU) have been widely applied in adhesive, leather, paints, leathers, textiles, and coatings. Herein, the reinforcement of 2 D nanosheets, graphene (Gr), graphene oxide (GO) and hexagonal boron nitride (h-BN) on the water resistance, mechanical and anti-corrosion properties of WPU was studied via in situ polymerization method with the loading amount of 0.25 wt%. Fourier Transform infrared spectroscopy analysis revealed no obvious changes in the internal structure of WPU incorporated with these 2 D nanosheets. The scanning electron microscope demonstrates a relatively homogeneous dispersion of h-BN in the WPU matrix. It is clear from the results that the resistance to water, mechanical and anti-corrosion properties of WPU were prominently improved by the incorporation of these nanosheets, especially h-BN, which was ascribed to its homogenous dispersion in WPU matrix and interface adhesion between polymer and filler. In the presence of 0.25 wt% h-BN, the water-absorption rate of WPU decreased from 37.3% to 15.7%, and the tensile strength improved from 4.16 MPa to 19.56 MPa. In conclusion, h-BN might be considered as an ideal nano-filler for WPU as compared to Gr and GO.